Football Nation: the playing fields of German culture, history, and society - Dawson, Rebeccah; Heinsohn, Bastian; Knabe, Oliver; McDougall, Alan (Berghahn, 2023)
Klappentext: Over the past century, the impact of football on Germany has been manifold, influencing the arts, political debates, and even contributing to the construction of cultural memories and national narratives. Football Nation analyses the game’s fluid role in shaping and reflecting German society, and spans its focus on modern German history, from the Wilhelmine era to the early 21st century. Expounding on topics of gender, class, fandom, spectatorship, antisemitism, nationalism, and internationalism, a diverse group of interdisciplinary scholars offer a novel approach to understanding the many influences of football throughout its extensive history which until recently has only been available to a German-speaking readership.
Keywords: Aufsatzsammlung; Geschichte 1871-2022; Kulturbeziehungen; Fußball; Deutschland; Kultur; Sozialgeschichte 1871-2022; Künste; Politik; Gesellschaft; Rezeption